PENGARUH STRUKTUR MODAL DAN LIKUIDITAS TERHADAP PROFITABILITAS BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rionita, Kadek; Abundanti, Nyoman (E-Jurnal Manajemen; Vol 7 No 8 (2018)DO - 10.24843/EJMUNUD.2018.v07.i08.p03, 2018)
Profitability is an appropriate indicator to measure the performance of a b ank. p rofitability assessment useful to determine the ability of companies in creating profit from capital used. This study aims to determine the effect of Capital Structure and Liquidity to Profitability of Bank Companies in Indonesia Stock Exchange. The population used in this study are all banking companies listed on the Indonesia Stock Exchange period 2013-2016. Sampling technique used is purposive sampling, based on sample determination criteria then the samples obtained are 33 banking companies listed on the Indonesia Stock Exchange period 2013-2016. Based on the results of the analysis found that the d ebt r atio has a negative significant effect to the r eturn o n e quity of the Bank companies in the Indonesia Stock Exchange, d ebt to e quity r atio have a positive significant effect to the r eturn o n e quity of the b ank companies in Indonesia Stock Exchange, l oan to d eposit r atio positive significant to r eturn o n e quity a b ank company on the Indonesia Stock Exchange.